Weak solvability of the unconditionally stable difference scheme for the coupled sine-Gordon system - Yildirim, Ozgur; Uzun, Meltem (Nonlinear Analysis: Modelling and Control, 2020)
In this paper, we study the existence and uniqueness of weak solution for the system of finite difference schemes for coupled sine-Gordon equations. A novel first order of accuracy unconditionally stable difference scheme is considered. The variational method also known as the energy method is applied to prove unique weak solvability.We also present a new unified numerical method for the approximate solution of this problem by combining the difference scheme and the fixed point iteration. A test problem is considered, and results of numerical experiments are presented with error analysis to verify the accuracy of the proposed numerical method.